Pemberdayaan Petani Kopi Kenjur Gunung Prau Kendal Melalui Pendampingan Strategi Pemasaran Digital - Mohammad Riza Radyanto; Antono Adhi; Enty Nur Hayati (Pusat Riset dan Inovasi Nasional, 2023)
The problem encountered by the Kenongo Sari Farmer Group in Purwosari Village, Sukorejo District, Kendal Regenc is the marketing aspect where coffee products for hotels, restaurants, and coffee shops were disrupted due to the effects of the Covid 19 Post Pandemic, where there was a decrease in turnover due to the closure of the coffee industry from upstream to downstream. In addition, the coffee produced by farmer groups located at the base of Prau Mount with a height of 1000 to 1400 MASL is less well known among Indonesian coffee connoisseurs, because the name Kenjur Coffee lacks promotion. Therefore this community service activity is carried out to promote and elevate the potential of Kenjur Cofee through the preparation of a digital marketing strategy. The method used is business assistance in creating social media, product branding, and conducting training for members. From the results of this 6-month assistance, it was obtained that there was a change in the mindset of business owners in implementing digital technology, having digital skills, and having media for promotion and marketing: Instagram social media, Google My Business, new logo, and new packaging. In the future, it is hoped that community service partners can increase turnover and have a wider range of product marketing